2004
DOI: 10.1101/gr.2004004
|View full text |Cite
|
Sign up to set email alerts
|

A Medaka Gene Map: The Trace of Ancestral Vertebrate Proto-Chromosomes Revealed by Comparative Gene Mapping

Abstract: The mapping of Hox clusters and many duplicated genes in zebrafish indicated an extra whole-genome duplication in ray-fined fish. However, to reconstruct the preduplication chromosomes (proto-chromosomes), the comparative genomic studies of more distantly related teleosts are essential. Medaka and zebrafish are ideal for this purpose, because their lineages separated from their last common ancestor ∼140 million years ago. To reconstruct ancient vertebrate chromosomes, including the chromosomes of the vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
210
2
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(230 citation statements)
references
References 27 publications
16
210
2
2
Order By: Relevance
“…According to karyotypic analysis, the gibel carp should be polyploid because it contains more than 150 chromosomes (Zhou and Gui, 2002). Recently, whole-genome duplication has been demonstrated in spotted green pufferfish (Jaillon et al, 2004) and medaka (Naruse et al, 2004), and three OlSpin genes identified from medaka have been deduced to stem from this similar duplication event (Wang et al, in press). The data implicate that more than one CagSpin genes may exist in the gibel carp genome, and significant sequence and functional divergence should have occurred among them.…”
Section: Discussionmentioning
confidence: 99%
“…According to karyotypic analysis, the gibel carp should be polyploid because it contains more than 150 chromosomes (Zhou and Gui, 2002). Recently, whole-genome duplication has been demonstrated in spotted green pufferfish (Jaillon et al, 2004) and medaka (Naruse et al, 2004), and three OlSpin genes identified from medaka have been deduced to stem from this similar duplication event (Wang et al, in press). The data implicate that more than one CagSpin genes may exist in the gibel carp genome, and significant sequence and functional divergence should have occurred among them.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane transporters that are the sites of action of diuretic drugs were first cloned from specialized organs in marine species (Gamba et al 1993;Xu et al 1994). Mutagenesis studies in bony fish generated a spectrum of biologically relevant and distinct phenotypes (Naruse et al 2004;Walter et al 2004). Large-scale genetic screens produced more than 500 zebrafish mutants, many with phenotypes similar to human disorders (Dooley and Zon 2000).…”
Section: The Contributions Of Marine and Freshwater Organisms To Compmentioning
confidence: 99%
“…Moreover, embryos are covered by a transparent egg chorion that allows direct observation of the development without interfering with the normal embryogenesis. Large-scale mutagenic screens in zebrafish and medaka have identified several orthologue genes that are related closely to those involved in human genetic diseases (Naruse et al, 2004). The response of zebrafish embryos to ethanol has been studied by many investigators and zebrafish have been recognized as a useful model for the study of alcohol-induced teratogenic effects (Bilotta et al, 2004;Carvan et al, 2004;Lockwood et al, 2004;Reimers et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese medaka, the Far East cousin of zebrafish (Wittbrodt et al, 2002), is rapidly emerging as an important model fish with regard to developmental biology and toxicology; these two species (zebrafish and Japanese medaka) separated from a common ancestor about 140 million years ago (Wittbrodt et al, 2002). Moreover, the spectrum and phenotypes of induced mutations in medaka is often different from those found in zebrafish (Ishikawa, 2000;Loosli et al, 2000;Naruse et al, 2004). In addition to genome size advantages between medaka and zebrafish (800 Mb in medaka and 1700 Mb in zebrafish), medaka is the only known nonmammalian vertebrate where the gender determining gene Sry and DMY were identified and characterized (Matsuda, 2005).…”
Section: Introductionmentioning
confidence: 99%